Method of determination of survival characteristics of weapons and military equipment - Volodymyr Dachkovskyi (Social Development & Security, 2020)
In order to repel armed aggression in the East of Ukraine, the national defense-industrial complex has modernized and developed a significant nomenclature of weapons and military equipment, which correspond to the forms and methods of conducting modern hostilities. Experience of using the samples of weapons and military equipment, which are allowed to exploitation in the Armed Forces of Ukraine, indicates on the necessity of resolving a number of problematic issues related to tecnical maintenance, repair, providing of logistical means etc., for keeping them in working order